Innovation and Growth: A Survey of the Literature and a Case Study for Latin America (2020)
This paper analyzes the recent literature on innovation and its determinants from an institutional point of view. Innovation is a concept that has been defined by several authors as implementing new ideas, processes, mechanisms and methods that allow the generation and development of new ideas, products, services and organization architectures. However, it is shown that the government, the universities and the private sector must converge in order to encourage the coevolution process of innovation. This is analyzed theoretically.